1993
DOI: 10.1073/pnas.90.6.2207
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation at threonine-235 by a ras-dependent mitogen-activated protein kinase cascade is essential for transcription factor NF-IL6.

Abstract: NF-IL6, a member of the basic leucine zipper (bZIP) family transcription factors, is involved in expression of inducible genes involved in immune and inflammatory responses. We observed that coexpression of oncogenic p2l1 stimulated the transactivating activity of NF-IL6 and induced phosphorylation of Thr-235 located just N-terminal NF-IL6 was initially identified as a nuclear factor binding to the interleukin 1 (IL-1) responsive element in the IL-6 gene (1). The cloned NF-IL6 exhibits a homology with CCAAT/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
375
2
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(406 citation statements)
references
References 33 publications
27
375
2
2
Order By: Relevance
“…Several transcription factors, such as Elk-1 (Gille et al, 1992;Marais et al, 1993), c-Myc , c-Jun Pulverer et al, 1991), c-Fos (O®r et al, 1990), NF-IL-6 (Nakajima et al, 1993), TAL-1 (Cheng et al, 1993) and AML-1 (Tanaka et al, 1996) have been proposed to be substrates for MAPK in vitro. Furthermore, it has been reported that Elk-1 (Rao and Reddy, 1994), c-Myc (Gupta and Davis, 1994) and AML-1 (Tanaka et al, 1996) can associate with MAPK in vitro, whereas AP-1 can associate with MAPK in vivo (Bernstein et al, 1994).…”
Section: Phosphorylation Of Bcl-6 By Mapk In Vivo M Moriyama Et Almentioning
confidence: 99%
“…Several transcription factors, such as Elk-1 (Gille et al, 1992;Marais et al, 1993), c-Myc , c-Jun Pulverer et al, 1991), c-Fos (O®r et al, 1990), NF-IL-6 (Nakajima et al, 1993), TAL-1 (Cheng et al, 1993) and AML-1 (Tanaka et al, 1996) have been proposed to be substrates for MAPK in vitro. Furthermore, it has been reported that Elk-1 (Rao and Reddy, 1994), c-Myc (Gupta and Davis, 1994) and AML-1 (Tanaka et al, 1996) can associate with MAPK in vitro, whereas AP-1 can associate with MAPK in vivo (Bernstein et al, 1994).…”
Section: Phosphorylation Of Bcl-6 By Mapk In Vivo M Moriyama Et Almentioning
confidence: 99%
“…The activation of p21ras signal transduction by a plethora of stimuli can lead to the phosphorylation of a number of transcription factors. These include: c-Jun (Binetruy et al, 1991;Pulverer et al, 1991), p62 TCF /Elk-1 (Marais et al, 1993), c-ets-1 (Co er et al, 1993;Galang et al, 1994;Giovane et al, 1994), NF-IL6 (Nakajima et al, 1993), c-Fos and c-Myc (Seth et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that phosphorylation of CEBPB on Thr 235 by ERK promotes the transcriptional activity of this transcription factor (14). Therefore, we assayed phosphorylation of the ERK-dependent site at Thr 235 of CEBPB in IL-1β-stimulated A549 cells.…”
Section: Erk-dependent Phosphorylation Of Cebpb Is Required For Il-1βmentioning
confidence: 99%
“…CEBPB3 (liver-enriched inhibitory protein; LIP) is 148 amino acids in length, and has been reported to function as a transcriptional repressor due to its lack of a transactivation domain (13). CEBPB becomes transcriptionally active when phosphorylated on Thr 235 (Thr 217 in the mouse) by the ERK2-stimulated kinase known as p90 ribosomal S kinase (14).…”
Section: Introductionmentioning
confidence: 99%